Metazoários parasitas de ciclídeos (Osteichthyes) americanos : testando hipóteses biogeográficas de diversidade de espécies. - Fernandes, Eliane da Silva (2017)
The central focus of biogeography and macroecology is to understand patterns of species distribution in space and time. Host-parasite interactions represent systems that link evolution and ecology by showing more broadly how biotic interactions occur along the geographic distribution. It is expected that the similarity between parasitic communities of cichlids from different ecoregions will decrease with increasing latitude. This study sought to understand how the intraáxons of parasites are distributed among local and global conditions, considering the geographic distance between hosts the main factor responsible for this distribution. The number of intrataxons of parasites varies both among hosts and within them, along their geographical distribution suggesting that some host taxa are more likely to be more parasitized than others. The following general biogeographic hypotheses were tested in this study: 1) the distributions of parasitic intrataxons have biogeographic limits determined by the host distribution; 2) host species tend to focus on certain regions of interfluves in the Brazilian basins. It was observed a greater similarity in the composition of the parasite community between Brazil and Mexico, Guatemala-Guyana, Peru-Venezuela and Argentina-Costa Rica, this equivalence in the parasite composition is due to some generalist species and probably due to introduced cichlid species. Although the Neotropical region is significantly richer in intrataxons parasites, it was not observed that with the increase of the latitudinal gradient the similarity between the parasites decreased, rejecting the hypothesis analyzed. Thus, the number of intrataxons parasites of cichlids increased towards the Equator and was verified in both regional and local scales, corroborating the hypotheses analyzed.